Efektifitas Terapi Seft dalam Menurunkan Hipertensi - Sunardi Sunardi; Edi Purwanto; Titin Sakinah (Journal of Ners and Midwifery, 2014)
Hypertension is a major problem in public health in Indonesia as well as in several countries in the world. The number of cases of hypertension is increasing very significantly from year to year. It is estimated that by 2025 in developing countries, an increase of about 80% of hypertension cases, from 639 million cases in 2000 to 1.15 million. Patients should receive complementary alternative therapies to reduce dependence on the use of drugs in reducing the symptoms of hypertension. SEFT therapy could theoretically be used to overcome the problem of an increase in blood pressure. The purpose of this study was to explain the effectiveness of the SEFT therapy to reducing blood pressure in patients with hypertension. Method: Research design was descriptive analytic method of pre - post test design with a case control approach. Samples specified quota sampling and sample size 30 patients with hypertension. Measuring instrument tensimeter diastolic blood pressure above 140 defined as patients with hypertension. Analysis using Independent T-Test Results. Result: The result showed that P-value = 0.023 (P <0.05). There was Â SEFT therapy have an influence on systolic blood pressure in patients with hypertension. Dicsussion: It is suggested for nurses to implementation SEFT therapy for hypertention patients to decrease blood pressure.